Age and body mass index associations with body segment parameters. (9th May 2019) - Merrill, Zachary; Perera, Subashan; Chambers, April; Cham, Rakié
Abstract: Body segment parameters (BSPs) such as segment mass, center of mass, and radius of gyration are required in many ergonomic tools and biomechanical models to estimate injury risk, and quantify muscle and joint contact forces. Currently, the full effects of age and obesity have not been taken into account when predicting BSPs. The goal of this study is to quantify the impact of body mass index (BMI) and age on BSPs, in order to provide more representative measures necessary for modeling inputs. A whole body dual energy X-ray absorptiometry (DXA) scan was collected for 280 working men and women with a wide range of BMI and aged 21 to 70 years. Established DXA processing methods were used to determine in-vivo estimates of the mass, center of mass, and radius of gyration for the upper arm, forearm, torso, thigh, and shank for males and females. Regression models were used to determine if age and BMI terms, as well as their interactions, were associated with these BSPs. The variability in BSPs explained by BMI alone ranged from 4 to 51%, and age explained an additional 3–19%. Thus, BMI and age are significant correlates of BSPs, and need to be taken into account when predicting certain BSPs in order to obtain accurate and representative results in biomechanical models.